Where Work Becomes Home: Domesticity and Spatial Resilience in Warung Madura - Dwi Putri, Adizza; Arvanda, Enira (RUAS, 2026)
Warung Madura, small convenience stores operated by Madurese migrants across urban Jakarta, represent a pervasive yet spatially understudied form of informal live-work space. This study examines domesticity within these environments as a condition where residential and commercial functions overlap. Domesticity is understood not merely as the presence of household elements, but as spatial and social practices that generate comfort, familiarity, and everyday meaning. Using visual ethnography approach, this research draws on field observations, visual documentation, and semi-structured interviews at two Warung Madura purposively selected from 15 mapped cases in Kelurahan Cipedak, analyzed through frameworks of urban domesticity, spatial appropriation, and live-work typologies. The findings indicate that domesticity is produced through flexible spatial arrangements, continuous negotiation between public and private uses, and social relations that foster attachment and a sense of spatial ownership, within contexts of economic precarity and unequal power relations between owners and caretakers.  Rather than functioning solely as sites of economic survival, Warung Madura emerged as meaningful spaces for identity formation, social interaction, and everyday urban life among low-income communities. This study contributes to discussions on urban domesticity, informal economies, and live–work typologies in dense urban environments, with particular relevance to Southeast Asian informal settlement contexts.